2021
DOI: 10.1002/jobm.202000657
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophytes: Molecular interactions with their hosts

Abstract: Plant growth promotion has been found associated with plants on the surface (epiphytic), inside (endophytic), or close to the plant roots (rhizospheric). Endophytic bacteria mainly have been researched for their beneficial activities in terms of nutrient availability, plant growth hormones, and control of soil‐borne and systemic pathogens. Molecular communications leading to these interactions between plants and endophytic bacteria are now being unrevealed using multidisciplinary approaches with advanced techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 256 publications
0
23
0
3
Order By: Relevance
“…Generally, host plants and rhizosphere endophytes are mostly symbiotic relationships. Previous studies have found that Azoarcus, Burkholderia, Gluconobacter, Herbaspirillum, Klebsiella, Plantoea and Rahnella and other bacterial genera can be detected in many plants (Dudeja et al, 2021). These bacteria can help host plants relieve nutrient stress by fixing nitrogen and secreting growth hormone under relatively infertile conditions (Dudeja et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, host plants and rhizosphere endophytes are mostly symbiotic relationships. Previous studies have found that Azoarcus, Burkholderia, Gluconobacter, Herbaspirillum, Klebsiella, Plantoea and Rahnella and other bacterial genera can be detected in many plants (Dudeja et al, 2021). These bacteria can help host plants relieve nutrient stress by fixing nitrogen and secreting growth hormone under relatively infertile conditions (Dudeja et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the endophytic bacteria undergo rhizophagy, biphasic cycle of alternation between the root intracellular phase (nutrients extracted by plants) and a free-living soil phase (acquisition of nutrients by bacteria) ( Dudeja et al, 2021 ). “Endobiome interference” is the term used to describe the phenomenon in which other endophytes interfere with rhizophagy and extract the nutrients from native microbes post-colonization.…”
Section: Plant Growth Promoting Endophytic Bacteria-assisted Biocontr...mentioning
confidence: 99%
“…The termite symbiotic system offers numerous opportunities for the discovery of new genes and enzymes. Recent advances in -omics, such as metaproteomics, metagenomics, and metatranscriptomics, have been used to elucidate the nature of this system [ 94 ]. Characterization and genetic engineering of these enzymes are essential for improving their suitability for industrial use.…”
Section: Yeast–termite Association and Significancementioning
confidence: 99%